Percepção dos cooperados quanto aos benefícios obtidos através do cooperativismo no sul de Minas Gerais - Soares, Lidiany dos Santos (2013)
In any agricultural activity, there is the existence of practices such as planting, creation, production and even industrialization, for the purpose of disposal of products and obtaining profits. The cooperative model presents itself as an organization that promotes social, economic development based on the union of people aimed at meeting the needs of the group, seeking growth set and not individually. The agricultural cooperatives are characterised by services provided to members, with receipt or marketing of joint production, storage and industrialization, as well as technical assistance, educational and social. The study examined the perceptions of members in relation to the benefits obtained through cooperatives and the vision of cooperatives in relation to their performance along to its cooperative members, having as main objective to evaluate the importance of cooperatives in agricultural market to its members through promotion of benefits that justify its existence. The method of investigation used guided by qualitative approach to analysis and interpretation of data collected and as methodological procedure was employed multiple case studies that allowed the survey data that contributed to the research problem raised elucidation. The data were collected through structured questionnaire with closed questions to cooperative members and interviews conducted by the three agricultural cooperatives of southern Minas Gerais. It was found that the satisfaction of cooperative members is strongly related to the fulfillment of demands financial and technical assistance, being considered as significant advantages of cooperative ties. Although cooperatives studied do not always offer the best prices, both in the sale of supplies as in the negotiations of the products deposited, there was the satisfaction of the majority of members, however, with little involvement or interest in decisions of cooperatives. The results revealed that although cooperatives are ease of access, unaware of the perception of their members in relation to the benefits and little participation are encouraged through cooperative courses and on the decisions taken in meetings.